Respon Pertumbuhan dan Produktivitas Tanaman Cabai Merah Keriting (Capsicum annuum L.) terhadap Jenis Media Tanam dan Berbagai Dosis Biochar - Sugito Loso; Haris Kriswantoro (Lembaga Pengembangan Kinerja Dosen, 2026)
Curly chili (Capsicum annuum L.) is one of the strategic horticultural commodities in Indonesia which has high economic value and plays an important role in meeting the food needs of the community. Biochar is a soil amendment with a high pore structure, which can increase water retention capacity, improve soil aeration, increase cation exchange capacity, and reduce nutrient loss due to leaching. he research was conducted at the experimental garden of the Faculty of Plant and Animal Sciences and the integrated laboratory at Campus B, Jalan Jenderal Besar Suharto KM 13, Lubuk Kupang, Lubuklinggau Selatan I, from February to May 2026. Using a Factorial Randomized Block Design (RAK) consisting of two factors. Factor 1: Type of Soil Media (P); P0 = topsoil, P1 = peat soil, P2 = ex-coal mining soil, P3 = marginal soil. Factor 2 Ameliorant Dose (K) K0 = no ameliorant (control), K1 = biochar 200 g/polybag, K2 = biochar 300 g/polybag, and K3 = biochar 400 g/polybag. Each treatment consisted of 3 sample plants repeated 3 times, the number of sample plants in each block was 16 treatments x 3 sample plants x 3 replications. Based on the research results, the type of planting medium and biochar dosage had the best effect on plant height, number of branches, flowering age, number of fruits, and fruit weight.